Diagnostic and prognostic value of c-MYC gene expression in hematological malignancies - Maryann Okafor, Ifeyinwa; Uchechi Okoroiwu, Henshaw; Ogar Ogar, Christopher (African health sciences, 2023)
Introduction: c-MYC plays vital role in regulation of cell proliferation and has been associated with tumorigenesis. This studyis aimed at assessing diagnostic and prognostic value of plasma c-MYC expression to aid in early diagnosis and prognosis ofhematological malignancies. Methods: Plasma c-MYC expression was determined by quantitative real time PCR using EVA Green chemistry and cluster ofdifferentiation markers performed via immunocytochemistry. Result: Plasma c-MYC was higher in subject with hematological malignancies (8.8 ± 1.1) when compared with apparently healthy controls (4.5 ± 0.5). A screening cut-off c-MYC ratio value of 9.42 with sensitivity and specificity of 65.5% and 100% respectively were obtained using receiver operator characteristic curve analysis. Plasma c-MYC was found to have no prognostic value using Kaplan-Meier analysis. Conclusion: Plasma c-MYC ratio showed promising screening/diagnostic value for hematological malignancies. Keywords: c-MYC; c-MYC screening; prognosis with c-MYC; hematological malignancies; plasma c-MYC; c-MYC in malignancies;c-MYC expression.